CRISPR/Cascade 9-Mediated Genome Editing-Challenges and Opportunities - Roy, Bhaskar; Zhao, Jing; Yang, Chao; Luo, Wen; Xiong, Teng; Li, Yong; Fang, Xiaodong; Gao, Guanjun; Singh, Chabungbam O.; Madsen, Lise; Zhou, Yong; Kristiansen, Karsten (Frontiers in Genetics, 2018)
CRISPR (Clustered Regularly Interspaced Palindromic Repeats) and Cascade provides protection from invading viruses. The CRISPR/Cascade 9 (CRISPR associated protein Cas9) system constitutes one of the most powerful genome technologies available to researchers today. So far, this technology has enabled efficient genome editing and modification in several model organisms and has successfully been used in biomedicine and biomedical engineering. However, challenges for efficient and safe genetic manipulation in several organisms persist. Here, we review functional approaches and future challenges associated with the use of the CRISPR/Cascade 9 genome editing system and discuss opportunities, ethical issues and future directions within this field.